2021
DOI: 10.1002/asia.202101069
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Pore Size, Basicity, and Binding Energy of Mesoporous C3N5 for CO2 Capture and Conversion

Abstract: We investigated the CO 2 adsorption and electrochemical conversion behavior of triazole-based C 3 N 5 nanorods as a single matrix for consecutive CO 2 capture and conversion. The pore size, basicity, and binding energy were tailored to identify critical factors for consecutive CO 2 capture and conversion over carbon nitrides. Temperature-programmed desorption (TPD) analysis of CO 2 demonstrates that triazole-based C 3 N 5 shows higher basicity and stronger CO 2 binding energy than g-C 3 N 4 . Triazole-based C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In addition, the reduction reactions frequently occur in liquid phases, where water competes with CO 2 to release H 2 from water reduction. [ 79 ] To enhance catalytic activities, the capacities to attract and store CO 2 on the surface of the materials play a central role in the reaction since adsorption is the first step in photocatalytic conversion. As exemplified by Park's work, mesoporous g‐C 3 N 5 exhibited superior CO 2 capturing abilities compared to activated carbons due to the strong interaction between the active nitrogen sites in g‐C 3 N 5 with CO 2 .…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
“…In addition, the reduction reactions frequently occur in liquid phases, where water competes with CO 2 to release H 2 from water reduction. [ 79 ] To enhance catalytic activities, the capacities to attract and store CO 2 on the surface of the materials play a central role in the reaction since adsorption is the first step in photocatalytic conversion. As exemplified by Park's work, mesoporous g‐C 3 N 5 exhibited superior CO 2 capturing abilities compared to activated carbons due to the strong interaction between the active nitrogen sites in g‐C 3 N 5 with CO 2 .…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
“…All the materials exhibit a peak around 100–250 °C. These peaks are due to physical adsorption of CO 2 on basic sites, and the amounts of basic sites can be estimated from peak size [38,39] . The peaks are prominent for the samples carbonized at 350 and 400 °C, however, they are small for the samples carbonized at 450 and 500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks are due to physical adsorption of CO 2 on basic sites, and the amounts of basic sites can be estimated from peak size. [38,39] The peaks are prominent for the samples carbonized at 350 and 400 °C, however, they are small for the samples carbonized at 450 and 500 °C. From these results, we can suggest the amounts of basic sites of MCN-350 and 400 are rich among all materials, resulting in their high catalytic performance in Knoevenagel condensation.…”
Section: Chemcatchemmentioning
confidence: 99%
“…Vinu’s group also synthesized g-C 3 N 5 nanorods with a combination of triazine and triazole groups, named MCN-14-X, using SBA-15 as a hard template instead of KIT-6. The preparation process is briefly summarized as follows: 5-ATTZ was impregnated into the porosity canals of the SBA-15 template, then carbonized for 4 h at 400 °C, and the template was etched with 5% HF acid to obtain MCN-14 [ 27 ]. The obtained mesoporous carbon nitrides, MCN-11 and MCN-14, have a good effect on the adsorption and conversion of CO 2 and are the catalysts for Knoevenagel condensation.…”
Section: Synthesis Strategies Of Pristine G-c 3 Nmentioning
confidence: 99%
“…Vinu et al [ 19 ] prepared the ordered mesoporous g-C 3 N 5 (MCN-8E-T) for CO 2 adsorption with 5.63 mmol g −1 of capacity at 273 K and 30 bar ( Figure 16 c). Vinu’s colleagues [ 27 ] also investigated MCN-14 materials with different pore sizes, which exhibit 5.6–9.1 mmol g −1 of CO 2 adsorption abilities at 0 °C and 30 bar and 14–38% of Faraday efficiencies for CO formation. Except for this conversion from CO 2 to CO, Morikawa et al [ 69 ] demonstrated that g-C 3 N 5 (-N = N-) can efficiently catalyze CO 2 to CH 4 and CH 3 CH 2 OH under visible light illumination by DFT calculation, with −0.54 eV ( Figure 16 d) and −0.61 eV ( Figure 16 e) of limiting potentials, respectively.…”
Section: Environmental and Energy Applicationsmentioning
confidence: 99%